Analysis of experience and prospects of mangiferin use in medicine and pharmacy - Polovko, Natalia; Yaromiy , Maryana (Annals of Mechnikov’s Institute, 2023)
Aim. Analysis of literature data and determination of the therapeutic potential of mangiferin and prospects for its use in medicine and pharmacy. Materials and methods. Electronic sources of information and a number of scientific publications of domestic and foreign scientists were used as research materials. The analysis was carried out on the basis of electronic databases for the period 2002-2022, which formed the empirical basis of the study. Logical, system-analytical, structural-functional and comparative methods of analysis were used. Results and discussion. Mangiferin is a biologically active ingredient, which is mainly isolated from the mango tree, has potent multifactorial pharmacological effects, including antioxidant, antidiabetic, antitumor, cardioprotective, neuroprotective, anti-inflammatory, antibacterial, antiviral and immunomodulatory effects. However, its low solubility and bioavailability limit the oral use of mangiferin as a clinical therapeutic agent, and chemical and physical modification is required to expand its use. Studies have shown the ability of mangiferin to penetrate through the stratum corneum and pass into the epidermis and dermis, which indicates the feasibility of using mangiferin in preparations for topical use. Conclusions.A significant number of published scientific studies conducted in vitro and in vivo confirm the diverse properties of mangiferin and that mangiferin has a high potential for use as an active pharmaceutical ingredient in the pharmaceutical industry and is promising for the development of new dosage forms and their further research. Keywords: mangiferin, antioxidant properties, antiviral activity, sources of mangiferin, application.